UROGENITAL CHLAMYDIOSIS: TACTICS OF MANAGEMENT AND PREVENTION OF PATIENTS - Baratova M.R. (PEDAGOGS, 2024)
Annotation: this article attempts to reveal the main reasons for the optimization of immunocorrection schemes in the treatment of urogenital chlamydia using an integral assessment of the state of various microbiocenoses of the human body. To carry out scientific work, the author studied the microflora of the mucous membranes of the vagina, cervical canal, urethra, prostate gland, urine samples, contents of the large intestine and peripheral blood in 193 patients (124 women and 69 men) with chronic chlamydial infection. The problem in question is still little studied, therefore, requires more thorough research.